2001
DOI: 10.1074/jbc.m009383200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Two Aquaporins Isolated from Native Spinach Leaf Plasma Membranes

Abstract: Two members of the aquaporin family, PM28A and a new one, PM28C, were isolated and shown to be the major constituents of spinach leaf plasma membranes. These two isoforms were identified and characterized by matrix-assisted laser desorption ionization-mass spectrometry. Edman degradation yielded the amino acid sequence of two domains belonging to the new isoform. PM28B, a previously described isoform, was not found in our preparations. Scanning transmission electron microscopy mass analysis revealed both PM28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 50 publications
6
72
0
1
Order By: Relevance
“…The bilayer integrity is markedly improved and holes disappear for the mixed DMPC/DMTAP bilayer ( Figure 9B), apparently due to the "electrostatic stitching" effect. The lateral dimensions of the smallest protruding features magnified in the inset C closely match the ~8 nm diameter of the aquaporin tetramer (Fotiadis et al 2001). The height of protrusions, about 2 nm above the surface of the DMPC bilayer, is also in good agreement with the known height of aquaporins.…”
Section: Incorporation Of Membrane Proteins Into Supported Biomimeticsupporting
confidence: 71%
“…The bilayer integrity is markedly improved and holes disappear for the mixed DMPC/DMTAP bilayer ( Figure 9B), apparently due to the "electrostatic stitching" effect. The lateral dimensions of the smallest protruding features magnified in the inset C closely match the ~8 nm diameter of the aquaporin tetramer (Fotiadis et al 2001). The height of protrusions, about 2 nm above the surface of the DMPC bilayer, is also in good agreement with the known height of aquaporins.…”
Section: Incorporation Of Membrane Proteins Into Supported Biomimeticsupporting
confidence: 71%
“…However, the characteristics of plant aquaporins at the single-molecular level have remained unclear. Although the structure of aquaporins has been clarified using x-ray crystallography and cryoelectron microscopy (Jap and Li, 1995;Fotiadis et al, 2001;Tö rnroth-Horsefield et al, 2006), no studies had reported on the oligomeric state of PIPs in the plasma membrane of living plant cells. Here, we imaged GFPlabeled PIP2;1 in the plasma membrane of root cells to determine its oligomeric state.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of aquaporins have been intensively studied, revealing the functions of their conserved motifs and post-translational modification sites, in water transport [3][4][5][6][7][8][9][10][11][12][13][14][15]. The expression patterns of aquaporin genes in response to salt, drought, cold, submergence, light, and phytohormones have also been characterized in various plants [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%